Democratic Education Transformation in Independent Curriculum - Pini Pitria; Firman; Dina Sukma (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The transformation of democratic education in the Independent Curriculum reflects an effort to create a more inclusive, adaptive, and learner-centered education system. Democratic education emphasizes freedom of thought, respect for individual rights, and active participation in the learning process. In the Independent Curriculum, this principle is realized through learning flexibility, the Pancasila Student profile, and the application of project-based learning. This article examines how the values of educational democracy are integrated into the Independent Curriculum, the challenges faced in its implementation, and the opportunities that can be utilized to improve the quality of national education. With a relevant and contextual approach, the Independent Curriculum is expected to be able to form a creative, critical, and globally competitive generation.